Risk factors and outcomes of vitamin D deficiency in very preterm infants - Hannah Cho; Yoon Lee; Saelin Oh; Ju Sun Heo (Pediatrics and Neonatology)
Background: Vitamin D is essential for bone health and immune system. Vitamin D deficiency (VDD) poses a high-risk to very preterm (VP) infants. This study aimed to evaluate the risk factors associated with VDD in VP infants and its potential clinical outcomes. Methods: A retrospective cohort study was conducted on VP infants admitted to the neonatal intensive care unit of a specialized tertiary hospital in Seoul, Republic of Korea, between January 2018 and June 2022. Serum 25-hydroxyvitamin D (25(OH)D) levels and other biochemical parameters were measured between 4 and 6 weeks of age. VDD was defined as a serum 25(OH)D level <20 ng/mL. Prenatal and postnatal risk factors and clinical outcomes were compared between the VDD and non-VDD groups. Results: Of the 82 VP infants analyzed, 27 (32.9%) were diagnosed with VDD. The VDD group exhibited a significantly longer duration of parenteral nutrition (PN) compared to the non-VDD group (adjusted odds ratio [OR] = 1.12; 95% confidence interval [CI]: 1.008–1.245). Breast milk intake was lower in the VDD group than in the non-VDD group (adjusted OR = 0.976, 95% CI, 0.955–0.999). Notably, calcium levels were significantly lower in the VDD group, while parathyroid hormone levels were significantly higher, compared with the non-VDD group. Additionally, the rickets severity score was higher in the VDD group than in the non-VDD, although the difference was not statistically significant. Conclusions: Prolonged PN duration and low breast milk intake significantly increased the risk of VDD in VP infants.